Radical Approaches to Political Science Roads Less Traveled - Rainer, Rainer (Verlag Barbara Budrich, 2012)
This ground breaking volume offers a range of alternative approaches to political science, highlighting problems too rarely confronted by "mainstream" political scientists. Ranging from Gunfighter Sagas to the changing faces of an imaginary Mars, the innovative chapters introduce whole new ways of rethinking politics, stirring up the all too conventional ways of the discipline.